The First Refinancing Of Railway Infrastructure In Indonesia: A Part of Public-Private Partnerships (PPP) - Helmi Adam; Adler Haymans Manurung; Roy Sembel; Jatmiko Murdiono (DINASTI RESEARCH, 2023)
Refinancing is an activity that can generate profits for the recipient. Carrying out refinancing can be a challenge for a company so it will make efforts well and optimally so that the refinancing is successful. This research uses a case study method by collecting data through interviews and documentation studies related to refinancing by PT Celebes Railway Indonesia (CRI). The aim of this research is to describe the refinancing carried out by PT CRI with the